Advances in neutrophil extracellular traps and ferroptosis in sepsis-induced cardiomyopathy - Zeng, Man; Niu, Yuying; Huang, Jiahao; Deng, Liehua (Frontiers in Immunology, 2025)
Sepsis-induced cardiomyopathy is a reversible non-ischemic acute cardiac dysfunction associated with sepsis. It is strongly associated with an abnormal immune response. It emerges as a vital threat to public health owing to its high mortality rate. However, the exact pathogenesis requires further investigation. In recent years, NETosis and ferroptosis, which are novel modes of programmed cell death, have been identified and found to play important roles in sepsis-related organ damage. This article outlines the mechanisms of these two modes of cell death, discusses the role of neutrophil extracellular traps in myocardial injury and the importance of ferroptosis in sepsis-induced cardiomyopathy, and reviews the potential interconnection between these two types of programmed cell death in sepsis-induced cardiomyopathy.